The Effect of Varied training style on The Development of Aerobic Endurance and Half Marathon Achievement for Men - AlJaf, Naween Azad Saleh; Al-Shamaa, Haider Faeq (Journal of Physical Education, 2021)
The research aimed at designing exercises and identifying the effect of varied training style on aerobic endurance development and men’s half marathon achievement. The researchers used the experimental method on (5) athletes who participated in championships for athletics’ clubs and Iraqi institutions for the year 2019. The researchers specified (10Km) and (21Km) tests, a pilot study was conducted, and then the training program was applied for four months with four training sessions per week. The data was collected and treated using proper statistical operations to conclude that aerobic endurance developed using varied training as well as achievement. Finally, the researchers recommended using modern training methods and styles that suits the sport in order to reach the optimal goal as well as making similar studies using varied training on other individual and team sports for both genders for different age groups. In addition to that, the researchers recommended using varied training on other physical abilities.